2016
DOI: 10.17306/j.afw.2016.4.30
|View full text |Cite
|
Sign up to set email alerts
|

The floral characteristics of the road edge effect on the example of a road with low traffic volume in the “Puszcza Notecka” Forest

Abstract: This paper concerns the edge effect of a provincial road on the broadly understood inventory characteristics of the neighbouring inland dune pine stands in the "Puszcza Notecka" Forest in Poland. The observations were conducted in the pine stands in the fresh coniferous forest and fresh mixed coniferous forest sites. Twelve rectangular experimental sites, called belt transects, were established perpendicular to the road axis. Each of them consisted of 3-4 plots located at different distances from the pavement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Both species are found in similar natural habitats in Poland Łukowski et al, 2017); however, black cherry can be observed growing in soil extremely poor in minerals or in heavily anthropogenically-transformed habitats . Moreover, these species are very common in the understory of urban forests and urban plantings (Dyderski et al, 2016), and often choose well-lit forest edges or roadsides (Mizera et al, 2016). Both species are therefore good model systems in which to study the impact of PM pollution, and the interaction of native and non-native plant species from the perspective of accumulation and response to PM pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Both species are found in similar natural habitats in Poland Łukowski et al, 2017); however, black cherry can be observed growing in soil extremely poor in minerals or in heavily anthropogenically-transformed habitats . Moreover, these species are very common in the understory of urban forests and urban plantings (Dyderski et al, 2016), and often choose well-lit forest edges or roadsides (Mizera et al, 2016). Both species are therefore good model systems in which to study the impact of PM pollution, and the interaction of native and non-native plant species from the perspective of accumulation and response to PM pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the morphology of both species’ leaves, however, may potentially explain the higher accumulation of PM on the foliage of P. padus (Danielewicz and Wiatrowska 2013 ; Popek et al 2017b ). Both plants are also found in similar natural habitats in Poland (Dyderski and Jagodziński 2015 ; Łukowski et al 2017 ); both are very common in the understory of urban forests and urban plantings (Dyderski et al 2016 ), and often choose well-lit forest edges or roadsides (Mizera et al 2016 ). Moreover, the leaves of P. padus and P. serotina are damaged by G. quinquepunctata more so than those of shrubs of other understory species (Karolewski et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%